2011
DOI: 10.4103/0250-474x.89755
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of malnutrition using modified subjective global assessment-dialysis malnutrition score in patients on hemodialysis

Abstract: Malnutrition is widely prevalent among patients on hemodialysis. Malnutrition can be estimated using a fully quantitative scoring system Subjective Global Assessment-Dialysis Malnutrition Score which is simple, reliable and dynamic. The primary objective of the study was to assess the severity of malnutrition in patients with end stage renal disease and undergoing hemodialysis in a tertiary care teaching hospital in Chennai, using Subjective Global Asses sment-Dialysis Malnutrition Score and correlate it with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 22 publications
4
31
1
5
Order By: Relevance
“…14,15 Both protein and the energy intake is reduced in chronic kidney disease because of the abnormal metabolism in peripheral as well as in hepatosplanchnic tissues. 16 The malnutrition indicators are serum.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Both protein and the energy intake is reduced in chronic kidney disease because of the abnormal metabolism in peripheral as well as in hepatosplanchnic tissues. 16 The malnutrition indicators are serum.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that MAC maybe a better marker for the nutritional and inflammatory status which was consistent with previous study. Janardhan et al showed that MAC was significantly correlated with dialysis malnutrition score [23]. Furthermore, Stosovic et al demonstrated that MAC was the most predictive anthropometric factor on mortality in hemodialysis patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Bunun yanında Beden Kitle İndeksi (BKI) beslenme durumunun belirlenmesinde kullanılabilecek basit ve objektif bir ölçümdür. Kreatinin kinetiklerinin de beslenme durumunun saptanmasında kullanılabilecek metotlardan biri olduğu söylenmektedir (12). Bioelektrik empedans (BIA), çift emisyon X-ray absorbsiyometri (DXA), nükleer manyetik rezonans, bilgisayarlı tomografi, total vücut potasyumu ve total vücut nitrojeni gibi gelişmiş diğer yöntemler de malnütrisyonun saptanması için kullanılabilmektedir (2,13).…”
Section: Malnütrisyonun Saptanmasıunclassified
“…Bioelektrik empedans (BIA), çift emisyon X-ray absorbsiyometri (DXA), nükleer manyetik rezonans, bilgisayarlı tomografi, total vücut potasyumu ve total vücut nitrojeni gibi gelişmiş diğer yöntemler de malnütrisyonun saptanması için kullanılabilmektedir (2,13). Beslenme durumunun değerlendirilmesi amacıyla oluşturulan formlardan biri olan Subjektif Global Değerlendirme (SGA) ve Protein Katabolizma Hızı (PCR) da kullanılan diğer yöntemler arasındadır (12,14). Biyokimyasal bulgulardan ise albümin, prealbümin, transferin ve insülin benzeri büyüme faktörü visseral proteinlerin değerlendirilmesinde kullanılabilir (2,11).…”
Section: Malnütrisyonun Saptanmasıunclassified
See 1 more Smart Citation